Effets antimicrobiens des extraits aqueux aux solvants à différentes polarités de RosmarinusofficinalisL chez Candida albicans - Bettahar, Khedidja (My University, 2019)
This work investigates the antifungal activity of extracts of RosmarinusofficinalisL harvested from two different regions of the country (Mostaganem and Naama) on the growth of Candida albicans involved in urogenital infections in female patients. The extracts were obtained by maceration of a plant intake in various aqueous solvents with increasing polarities including: hexane, methanol, ethanol and water. The extracts recovered after evaporation were then concentrated at 0, 20, 40, 60, 80 and 100%, respectively. The measurements and controls carried out in triplicate tests on the various experimental extracts concerned: the growth test, the disk diffusion test, the determination of the minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (CMF). The data were statistically analyzed for bifactorial variance in randomization and a comparison of mean two-to-two values. The aqueous extracts with solvents with different polarity of Rosmarinusofficinalis L harvested in Naama and Mostaganem showed in particular in the pure state and at a concentration of 80% an antimicrobial effect of fungicidal type vis-à-vis the microbial species Candida albicans . At these concentrations no growth of this microorganism was observed and the diameters of inhibitions demonstrated by the agar diffusion test were remarkably similar to those of gentamicin considered as a powerful broad-spectrum antibiotic.
Keywords: Rosmarinusofficinalis L; extracts; solvent; polarity; activity; antifungal; Candida albicans